Recommendation‐making in the emergency department: A qualitative study of how Canadian emergency physicians guide treatment decisions about resuscitation in critically ill patients - Henry Ajzenberg; Katie N. Dainty; Erin O'Connor (Journal of the American College of Emergency Physicians Open)
Abstract Study Objective Emergency physicians are frequently responsible for making time‐sensitive decisions around the provision of life‐sustaining treatment. These decisions can involve goals of care or code status discussion, which will often substantially alter a patient's care pathway. A central part of these conversations that has received relatively little attention are recommendations for care. By proposing a best course of action or treatment via a recommendation, a clinician can ensure that their patients receive care that is concordant with their values. The objective of this study is to explore emergency physicians’ attitudes toward recommendations about resuscitation in critically ill patients in the emergency department (ED). Methods We recruited Canadian emergency physicians via multiple recruitment strategies to ensure maximum variation sampling. Semi‐structured qualitative interviews were conducted until thematic saturation occurred. Participants were asked about their perspectives and experiences with respect to recommendation‐making in critically ill patients and to identify areas for improvement in this process in the ED. We used a qualitative descriptive approach and thematic analysis to identify themes around recommendation‐making in the ED for critically ill patients. Results Sixteen emergency physicians agreed to participate. We identified four themes and multiple subthemes. Major themes included identification of the roles and responsibilities of the emergency physician (EP) with respect to making a recommendation, the logistics or process of making a recommendation, barriers to making a recommendation, and how to improve recommendation‐making and goals of care conversations in the ED. Conclusion Emergency physicians provided a range of perspectives on the role of recommendation‐making in critically ill patients in the ED. Several barriers to the inclusion of a recommendation were identified and many physicians provided ideas on how to improve goals of care conversations, the recommendation‐making process, and ensure that critically ill patients receive care that is concordant with their values.